Factors affecting growth performance of sheep under village management conditions in the south western part of Ethiopia - Bela, B.; Haile, Aynalem (2009)
The study was conducted to assess the growth performance of lambs under village management condition in Jimma, Ethiopia from 1995 to 1997. The overall mean body weight at birth, at weaning (180 days) and up to a year (360 days) was recorded to be 2.45, 18.8 and 25.4 kg, respectively. The overall mean growth rate up to weaning weight (180 days) and up to one year old (360 days) was 92.3 and 68.3 g/day. The non-genetic factors such as season, yea, sex, parity, litter size and district were considered in this study. The main factors had a significant effect (at least p<0.05) on weight for age and weight gains recorded. A consistent significant effect of sex and birth type (single/twin) (p< 0.05) was observed for weight for age and growth rates. The males were heavier than females, by 7.11% and 10.2 % for 180 days and 360 days weight, respectively. The twins were lighter than singles by 20.1 % and 8.32% for 180 days and 300 days weight, respectively. The effect of parity was significant (p<0.05). The lambs born to ewes at first parity had lower weight for ages and weight gains compared to subsequent parities. The lambs born in land scarce area (Dedo district) had lower weight gains than lambs born in Seka (land better area). Differences were significant (P<0.05) and weight gain recorded at 180 days were 85.3 and 90.9 g/day for Dedo and Seka lambs, respectively. The variation in growth performance of sheep in different districts could provide base line information to set a long-term genetic improvement plan by election. The results are discussed in comparison with data obtained from elsewhere in the tropics.